The involvement of the brain microenvironment in Alzheimer’s Disease - Fuso, Andrea (Organisms. Journal of Biological Sciences, 2018)
The recent decision by some “pharma company” to abandon the research in the field of Alzheimer’s Disease should not scare the patients and their familial: many other companies and research institutes are strongly working with the attempt to find a cure, a preventive treatment and efficient early diagnosis tools. On the other hand, the risen white flag should worry the same researchers: it is the sign that, in general, a wrong approach has been probably pursued. The failure of the current clinical trials relies on the attempt to treat the neurodegenerative process targeting single effectors of the Disease. It is becoming more and more evident that, as a multifactorial disease, Alzheimer’s has to be considered as a systemic pathology in which different biochemical and molecular pathways are involved as well as different cellular population or even different tissues. The road to approach to Alzheimer’s through systems biology or medicine is maybe still long, but we already have the background to consider the role of the whole brain microenvironment in the onset and progression of the disease. Glial cells, brain vasculature and blood-brain-barrier clearly play a relevant role in Alzheimer’s Disease through the production of several molecules that can influence the (patho)physiology of the neuronal cells. Particularly promising seems the study of the possible epigenetic modifications induced in neurons by the alterations of the brain microenvironment.